ANALYSIS OF THE END OF THE KURDISTAN PARTIYA KARKERÊN TERRORIST ORGANIZATION IN TURKEY - Pradnyana, I Putu Hadi; Rofii, Muhammad Syaroni (Journal of Terrorism Studies, 2020)
This paper analyzes the end of the Partiya Karkerên Kurdistan (PKK) in Turkey. The PKK is a terrorist organization based on the aim of separatism from Turkey. Since its founding in 1978 until now, various acts of terror have been carried out by the PKK and Turkish authorities view the PKK as the most dangerous terrorist organization in its territory. The type of research used is descriptive qualitative. Politicization factors are the main variable in analyzing the end of the PKK in Turkey. The result of the analysis is that the PKK will soon end through constitutional agreements through Kurdish representatives in the Turkish parliament which were won by HDP, a pro-Kurdish political party. HDP's success as the first pro-Kurdish party to enter the Turkish parliament even broke the 10% threshold, becoming an important momentum for the PKK and the Turkish government to conduct constitutional negotiations. Keywords: terrorism organizations, Partiya Karkerên Kurdistan (PKK), Turkey, politicization.